Laboratory Testing of Rediffusion of Contaminants Using DKS-Permeameter - Székely, István; Kovács, Virág; Madarász, Tamás (International Journal of Engineering and Management Sciences, 2018)
Decades long hydrocarbon contaminations effecting heterogenous groundwater systems is a common problem both in Hungary and worldwide. Only the treatment of aquifer layers is possible with remediation technologies, so the contaminations remained in the aquitards are released back to the treated porous layer  after the treatment due to the changes in concentration-gradient. This process is the so-called back-diffusion: as a result, the previously removed contaminations appear in the remediated layer again. In order to get better understanding of the rediffusion process and the influencing parameters series of measurements were carried out at the University of Miskolc Faculty of Earth Science and Engineering using a special laboratory device called DKS-permeameter. With the help of some small modifications it can be used for the modeling of backdiffusion. Artificially contaminated soil samples were built in the DKS-permeameter from which contaminanant release occured due to back-diffusion. The concentration values were determined with spectrophotometric measurements.